The Association of Severe Toxoplasmosis and Some Cytokine Levels in Breast Cancer Patients - Assim, Maha Mustafa; Saheb, Entsar Jabbar (Iraqi Journal of Science, 2018)
Toxoplasma gondii is an opportunistic pathogen in which the reactivation of a latent infection can cause death in congenitally infected fetuses, newborns, and immunocompromised patients. This study aimed to determine the seropositivity of toxoplasmosis infection and the possible association with Interleukin-12 (IL-12) and Interleukin-23 (IL-23) cytokines in breast cancer patients. In this study, 190 women were enrolled. All serum samples were tested for T. gondii immunoglobulins (IgG and IgM) antibodies and (IL-12, IL-23) levels using ELISA technique. The result of this study showed that breast cancer patients recorded the highest percentage of toxoplasmosis infection. There were no positivity rates for anti- Toxoplasma IgM in breast cancer patients while the positivity percentage for anti- Toxoplasma IgM among the control group was (7.00%). Furthermore, the seroprevalence of anti- Toxoplasma IgG was the highest in the age group (31- 40) years in patients with breast cancer while the highest mean titer of the IL-12 is restricted to ages (20-30) years in the control groups who are seropositive to anti- Toxoplasma IgG. Although, in patients with breast cancer who are seropositive to anti- Toxoplasma IgG, the highest mean titer of the IL-23 was in ages (20-30) years. Since most immunosuppressive patients are exposed to various possible risk factors including Toxoplasma primary infection or reactivation, so it is important to diagnose and treat toxoplasmosis in breast cancer patients to reduce the consequences of the infection.